2021
DOI: 10.1044/2021_aja-20-00150
|View full text |Cite
|
Sign up to set email alerts
|

Disposable Hearing Aid Battery Management: Survey Assessment of Providers and Qualitative Interviews of Patients

Abstract: Purpose The purpose of this study was to better understand the behaviors that hearing aid users engage in to manage batteries. Method Two arms of research, a survey of audiologists ( n = 110) and qualitative interviews with adult hearing aid users ( n = 13), were conducted. Surveys were distributed and collected both via paper and online methods. Descriptive analyses of survey result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The energy consumption of the best integrated devices in the literature reaches up to 17 J for a 10 h period of daily use [ 1 , 2 , 3 ]. Woodruff et al underlined that patients using hearing aids sometimes struggle to change and select disposable batteries for their devices [ 4 ]. Another statistical study recently revealed that the rechargeable batteries have the most positive impact on customer’s listening experience [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The energy consumption of the best integrated devices in the literature reaches up to 17 J for a 10 h period of daily use [ 1 , 2 , 3 ]. Woodruff et al underlined that patients using hearing aids sometimes struggle to change and select disposable batteries for their devices [ 4 ]. Another statistical study recently revealed that the rechargeable batteries have the most positive impact on customer’s listening experience [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although hearing services are included in universal health coverage, hearing devices require maintenance. Changing batteries could impose both mechanical and financial challenges ( 27 ). Previous studies also highlighted handling problems and volume control ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…27 Alternatively, a probabilistic monotonic echo state network algorithm is used to follow the nonlinear battery aging process on the basis of the time interval associated with the sequence of voltage declines during battery capacity and discharge. 28 Benefits of this approach are that only a portion of the battery charge/discharge test is required for SOH estimation; 29 as well as being comparatively simple and accessible to implement, 30 although the extraction of feature maps requires consideration of various elements and extensive workload. 31 Data-driven based approaches take battery test data as the initial sample, withdraw the evolution law of battery performance during battery degradation by some mechanisms, and then utilize this regularity for SOH estimation.…”
mentioning
confidence: 99%